Rapid qualitative and quantitative HPLC/MS analysis of ethylenediaminetetraacetic acid in a pharmaceutical product without prior sample preparation - Stanislav V. Yefimov (GarVal Editorial Ltda., 2020)
Context: Sodium calcium ethylenediaminetetraacetic acid (EDTA) is used to bind metal ions in the practice of chelation therapy, such as treating mercury and lead poisoning. This therapy is used to treat the complication of repeated blood transfusions, as would be applied to treat thalassemia. The work is devoted to the analysis of EDTA in pharmaceutical products. Aims: To develop and validate a fast method for qualitative and quantitative estimation of EDTA in pharmaceutical products without derivatization. Methods: The Agilent 6125 C SQ LS/MS instrument was used. Mass Spectrometer was chosen to detect EDTA directly without derivatization and any preliminary sample preparation. Results: The method was validated in accordance with International Conference on Harmonization guidelines. Total run time was 1.0 min. EDTA was eluted with a retention time of 0.23 ± 0.01 min. The limit of detection was 0.09 μg EDTA. Recovery varied from 100 to 113% and the relative standard deviation varied from 0 to 6%. In positive Electrospray ionization mode, the spectra showed the predominant signals at m/z of 293.2 which corresponds to cation (EDTAH+) and 315.2, which corresponds to cation (EDTANa+). Conclusions: The developed HPLC/MS method for the determination of EDTA in pharmaceutical preparations containing various other ingredients, including excipients (NaOH and benzyl alcohol), was validated for linearity, accuracy/recovery, precision and selectivity, as well as low detection limit and quantification. The method provides a fast, simple, sensitive and reproducible means of determining the pharmaceutical compositions of EDTA without derivatization and prior sample preparation.